LEGAL POLICY AS A MEANS TO IMPROVE LAWMAKING PROCESS - Alexander Vasilyevich Malko (Astra Salvensis, 2019)
Presently the general theory of law does not provide a throughly explored definition for legal policy. The material suggested by the authors considers both the discussion on the legal policy itself as a phenomenon of law and state and the analysis of the legal policy possibilities in the sphere of lawmaking improvement. Legal policy being a means of democratic transformations in a society can develop and further achieve many important purposes of strategic nature. The authors use different general and specific scientific methods in conducting their research. However, the study is based on the method of sociological analysis, including the results of the sociological survey carried out with the participation of the Social and Political Research Center in Saratov State Academy of Law and Scientific Educational Center of Federal and Regional Issues in Legal Policy in Saratov Branch of the State and Law Institute of the Russian Academy of Sciences. The paper looks at the nature and the content of the phenomenon from different perspectives. The authors believe that it is impossible to implement all other types of policies in a civilized manner with no legal policy in the modern context. The authors offer to specify policy‟s special type-lawmaking policy served to be the basis for the comprehensive development of the law system. The features of this phenomenon, the features of its interaction with other spheres of the legal policy and the state policy on the whole are stated. It is concluded that the lawmaking policy plays a special role as a multi-purpose means to improve the lawmaking process in the context of modern Russia.